The study of peculiarities of pasteurized dairy products of Osakarov district - Kartbayeva, G.Т.; Elshina, K.А. (Вестник Карагандинского университета, 2016)
The article presents the characteristics of milk before and after pasteurization. Depending on the season, changes of microbiological composition of milk and its dynamics are given. Physical and chemical characteristics of cow's milk are described. The complete composition of cow's milk of this district is described and also a comparative characteristic is given. Analysis of cow's milk is made. Comparative characteristics of home milk and milk from a store also were presented in this article. A biological composition, fat content and protein content are considered.
Keywords: pasteurization; sterilization; autoclave; lacto densimeter; innovation; dynamics